(untitled) (DIGITAL TRANSFORMATION AND ARTIFICIAL INTELLIGENCE, 2024)
This article discusses the main aspects of personal data and its de-identification as an information protection measure. It also describes the risks of re-identification and the causes of attacks related to this phenomenon and demonstrates the process of collecting, processing and de-identifying personal data.